Trabalho e Universidade: um estudo sobre a (de)formação no ensino superior brasileiro - Rondon, Roberto (2006)
In the present study, we sought to establish a critical analysis of the centrality of work as a forming principle in Brazilian higher education. With this intention, we introduced a discussion over the concept of work through the ages until the emergence of the capitalist society, which brought the idea of regarding it as a forming principle of our own subjectivity and of our way of being in the world. Beside this, we outlined a reflection about the path of higher education, highlighting the historical transformations that have led to the creation of modern University, which in turns represents the origin of the models developed in Brazil, where such institutions emerged late. With basis on such reflection, we discussed some aspects of higher education in Brazil. We tried to rescue its roots, development and main characteristics, evaluating the extent of its past – and present – contribution to the reproduction of the insane way of life modern society has adopted, tied to the one-dimensional logics of work, which became deeper between the late 1970s and the beginning of the XXI century.